Etiopathogenesis of Post-endodontic Periapical Scar Formation - Edita Horká; René Foltán; Tomáš Hanzelka; Gabriela Pavlíková; Karel Klíma; Jiří Šedý (Wolters Kluwer Medknow Publications, 2012)
Introduction: A periapical scar represents a clinically asymptomatic, non-progressive, small, periapical radiolucency in patients with a previously well-performed root canal treatment.The hypothesis: We introduce a hypothesis that periapical scar formation is caused by osseoinhibitory molecular signaling from the epithelial cell rests of Malassez.Evaluation of the hypothesis: When epithelial cell rests of Malassez are present in teeth with an infected root canal system, a periapical cyst develops, whereas in the case of a treated root canal system infection, periapical inflammation is diminished and the periapical leasion heals until the regeneration process reaches the apical part of the tooth where epithelial cell rests of Malassez are present. Cytokines cause rapidly progressive defensive fibroproduction and scar formation, in which osteoblasts cannot differentiate into